Enhancing Spatial Ability: A New Integrated Hybrid Training Approach for Engineering and Architecture Students - Ronen Porat; Ciprian Ceobanu (MDPI AG, 2024)
Spatial ability (SA) is the mental ability to create, maintain, and manipulate abstract visual representations. Studies have shown that SA is a strong predictor of success in the fields of science, technology, engineering, and mathematics (STEM). More recently, attention has extended to the field of architecture, a discipline where spatial thinking skills are fundamental, yet students in this field have not been extensively examined in terms of their spatial abilities. Therefore, SA skills are essential for students in engineering and architecture during their initial academic phases. This research was conducted within an interdisciplinary academic college and describes in detail a new integrated and hybrid training program that is part of a recent mixed-methods study. This program was built to effectively enhance the SA of first-year undergraduate students in a cost-effective manner, using a multi-method teaching strategy. The training program spanned more than 20 h across four sessions. This article focuses on the training methodology, encompassing four key phases, and serves as a complementary article to the one that was just published separately, describing the effectiveness of this intervention program as measured using SA standard tests. Notably, in certain scenarios, these phases were combined rather than being standalone independent modules. The traditional teaching method (TTM) lays the foundation for SA knowledge via lectures and collaborative interactions. Subsequently, computer-based learning (CBL), using tools such as SketchUp and GeoGebra, facilitates in-depth virtual geometric exploration. Augmented reality (AR) training offers an immersive learning experience, allowing students to interact with 3D objects in real-world environments. Finally, the building real model (BRM) phase transforms 2D designs into tangible 3D structures. This study highlights the comprehensive training approach, emphasizing the robust learning environment facilitated by integrating these phases as part of the full mixed-methods research. The suggested integrated training program was qualitatively explored through post-intervention evaluations to understand participants' experiences and perceptions.